BIMBINGAN KEAGAMAAN DALAM MENINGKATKAN RELIGIUSITAS SISWA DI SEKOLAH DASAR ISLAM TERPADU - Fadhil Hardiansyah; Nafi'ah Uswatun (Jurnal Bimbingan Penyuluhan Islam, 2023)
Religious guidance is an effort to provide asssistance to a person who face problems using a religious approach so that they can awaken inner strength to encourage them to overcome the problems they face. The formulation of the research problem is the role of religious guidance in increasing the religiosity in aspects of worship and aqidah of class VI students at SDIT in Metro City. This research aims to analyze the role of religious guidance in increasing religiosity aspects of worship and aqidah of class VI SDIT in Metro City student. This type of research is field research with a qualitative descriptive nature. The resources persons in this research were 8 students, homeroom teachers and religious advisors. Data collection tools include observation, interviews and documentation. Based on the results, religious guidance at SDIT in Metro City has an important role in increasing student religiosity to improve the morals or behavior of class VI students at SDIT in Metro City. Religious guidance is provided in a directed manner to students through aspects of faith and worship in the form of delivering material and practice. This can be seen through the religious guidance program on the aqidah aspect, namely getting to know the companions of the Prophet Muhammad SAW, explaining the Prophet's Sirah, the pillars of faith and observing all of Allah's creation. Meanwhile, aspects of worship include Duha Prayer, Midday Prayer, Women's Fiqh, Learning to Read the Koran, Tahsin and Tahfidz, Getting to Know Fasting, Zakat, Explanation of Hadith 21 Arba'in Nawawiyah.